Measuring Engagement Index On Millennial Employee At Vocational Higher Education - Avy Luthfiana; Indrawati Yuhertiana (LPPM of NAROTAMA UNIVERSITY, 2021)
EMPLOYEE ENGAGEMENT greatly affected employee performance. The purpose of this study was to determine the indeks of employee engagement on millennial employee at vocational higher education in Indonesia. The total number of respondents was 95 people from two vocational higher education in East Java. From the results of 4-point Likert scale questionnaire analysis, it was known that the engagement index of millennial employees in vocational higher education was partially engaged with an engagement index of 2.90. The average engagement index for lecturers was higher than that of non-lecturer employees. From these two groups, it was found that the same dominant and less dominant factors were the same; the highest value namely Motivation Value and the lowest was Communication Value. The results of regression analysis showed that all aspects of the independent variables simultaneously affect employee engagement. Efforts to increase the level of employee engagement among millennial employees in vocational PTN are focused on aspects that receive low ratings, including communication, relationships with work and organizations, and remuneration. Employees asked for motivation system based on incentives, and socialization about the remuneration and compensation system.